A PARAMETRIC ANALYSIS OF AN OCEAN WAVE ENERGY HARVESTING SYSTEM - Marques, Carlos Eduardo; Balthazar, José Manoel; Rocha, Rodrigo Tumolim; Tusset, Ângelo Marcelo; Janzen, Frederic Conrad (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
In this paper, we present some parametric analysis of an ocean wave energy harvesting system. The mathematical model of a floating ocean platform attached to a DCÂ motor is considered to use the ocean waves to generate electrical energy. A pendulum wasÂ coupled to the DC motor axis, transforming the vertical excitation of the floating platformÂ into rotation movements of the generator, then varying the magnetic flux of the permanent magnets of the motor, generating electric energy. In order to optimize the power generation, we present a study of mass settings of the pendulum and an ocean wave amplitudes analysis, based on Maranhão’s coast characteristics. The dynamic behavior of the system is shown through numerical simulations, as well as the efficiency of conversion of the pendulum swings in electricity.Â Keywords: Pendulum System, Mathematical Modeling, Energy Harvesting, Ocean WaveÂ Energy.